Oxygen‐Defected Molybdenum Oxides Hierarchical Nanostructure Constructed by Atomic‐Level Thickness Nanosheets as an Efficient Absorber for Solar Steam Generation. Issue 2 (30th November 2018) - Lu, Qichen; Yang, Yong; Feng, Jianrui; Wang, Xun
Abstract : Solar steam generation is a potential approach for fresh water recycling, thus attracting increasing attention recently. To further promote water evaporation rate, some new materials need to be developed, such as plasmonic transition metal oxides. In this work, we report an oxygen‐defected molybdenum oxides hierarchical nanostructure (MoOx HNS) composed of ultrathin nanosheets with atomic‐level thickness, which is demonstrated as an efficient absorber for solar steam generation. Benefiting from broadband light absorption and special assembled architecture, the resulting MoOx HNS loaded on a PTFE membrane (MoOx HNS Membrane) exhibits excellent performance for boosting steam generation rate. Under 1 sun (1 kW m −2 ) illumination, the evaporation rate can reach at 1.255 kg m −2  h −1, with the energy conversion efficiency of 85.6%, which is one of the best performance compared with other desalination materials. Meanwhile, the MoOx HNS Membrane can achieve high‐performance seawater desalination in both laboratorial and outdoor conditions. The enhanced water evaporation performance can be attributed to the synergistic effects of the efficient solar‐to‐thermal conversion and the unique channel structure. This work expands the scope of investigated materials which can be applied in seawater desalination system. Abstract : MoOx HNS is synthesized and demonstrated as an efficient absorber for solar steam generation. Under 1 sun illumination, the evaporation rate can reach 1.255 kg m −2  h −1, with an energy conversion efficiency of 85.6%. This enhanced performance can be attributed to the synergistic effects of the efficient solar‐to‐thermal conversion and the unique channel structure.